Penerapan Bimbingan Konseling di Taman Kanak-Kanak pada Anak Usia Dini di Desa Timbang Lawan - Ade Anggraini Hasibuan; Ahsanul Hakim Hasibuan; Leni Mayarani; Lenni Dalimunthe (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
RI Law No. i20/2003 states that early childhood education can be carried out through formal, non-formal and informal education channels. Early childhood education is formal in the form of Kindergarten (TK), Raudhatul Athfal (RA) or similar forms, non-formal in the form of play groups (KB) and other forms that are equivalent. Counseling Guidance as an activity to avoid or overcome problems in life. The basic assumption that underlies that PAUD needs guidance and counseling is the current equality of PAUD with primary and secondary education. Early childhood from the age of 10-5 years is the golden age in the human brain development phase. This is sometimes not realized by parents who tend to be indifferent to children's brain development. This problem is very serious if the child's brain development is not known by parents, because it can have an impact on adulthood later. That person should prepare for the golden age. Because during the golden age, children are very easy to remember new things. It's a real loss if parents just let their children grow and develop as they please without any guidance from their parents at all. Keywords: counseling guidance, kindergarten, early childhood